Multicentre case-control study on the association between COVID-19 vaccines and neurological disorders (COVIVAX) - Elisabetta Pupillo; Elisa Bianchi; Ettore Beghi; Francesco Andrea Pedrazzini; Angela Giglio; Edoardo Dalmato Schilke; Marco Percetti; Carlo Morotti Colleoni; Gabriele Mainini; Paolo Calabresi; Guido Primiano; Giovanni Frisullo; et al. (Scientific Reports)
Abstract The COVIVAX study assessed the association between COVID-19 vaccination and the risk of common neurological disorders in a multicenter case-control design. Vaccination exposure was compared between individuals with a first diagnosis of a neurological disorder (cases) and age- and sex-matched controls. A total of 624 participants were enrolled, and after random 1:1 matching 265 cases and 265 matched controls (total 530 participants) were included in the analyses. The most frequent neurological diagnosis in cases were stroke (60.4%), multiple sclerosis (11.3%) and seizures (6.4%). The proportion of vaccinated participants was 72.1% among cases and 79.6% among controls. A protective role of vaccination on the risk of developing a new neurological disorder was detected in the unadjusted analysis (OR 0.50; 95% CI 0.29–0.86; p = 0.0114). After adjustment for confounders, the number of vaccination doses received was associated with a reduced risk of developing new neurological disorders for participants aged over 60 years ( p = 0.0472; OR 0.14, 95% CI 0.03–0.68), with pre-existing comorbidities (p = 0.0122; OR 0.04, 95% CI 0.01–0.99) and for stroke (p = 0.0232; OR 0.04, 95% CI 0.02–0.97). The COVIVAX study provided no warning sign regarding an increase in the risk of developing new neurological disorders following COVID-19 vaccination of any type or doses. A potentially protective effect of multiple doses of COVID-19 vaccines against the risk of stroke in people aged over 60 needs to be confirmed by further studies.